THE EFFECT OF ENGLISH AS AN OPTIONAL SUBJECT AT ELEMENTARY SCHOOL TOWARDS JUNIOR HIGH SCHOOL ENGLISH PRODUCTIVE SKILL (A Study at SMPN 26 Kota Serang): PENGARUH BAHASA INGGRIS SEBAGAI MATA PELAJARAN PILIHAN DI SEKOLAH DASAR TERHADAP KEMAMPUAN PRODUKTIF BAHASA INGGRIS DI SEKOLAH MENENGAH PERTAMA (Studi di SMPN 26 Kota Serang) - Rachmatia; Nurhaeda Gailea; Eri Rahmawati (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2026)
The text of the 2022 National Education System draft law in August in article 81, paragraph 1, explains that English is an optional subject at elementary school and reaps many cons. English has a significant role in helping the next generation of Indonesians to grow up better academically, especially in productive speaking and writing skills. Of this problem, the researcher wanted to seek out the effect of English as an optional subject in elementary school on junior high school English productive skill. The researcher used a mixed method with the ex-post facto design, where quantitative data were processed before qualitative data. Questionnaires, interviews, and open-ended tests were used to gain the data. All the data analyses were counted on SPSS. The respondents were 45 students at SMPN 26 Kota Serang with criteria for 7th-grade JHS students who previously had English as an optional subject. The results showed negative and non-significant simultaneous effects between learning English as an optional subject at Elementary school towards Junior High School students’ English productive skills with an f-value of 0.154 with a significance value of 0.858 (far above 0.05). The students struggled to improve their speaking and writing skills in junior high school due to the lack of active practice opportunities. This results in a lack of foundational English skills and difficulty meeting higher standards at Junior High School.